2009
DOI: 10.1002/jsfa.3682
|View full text |Cite
|
Sign up to set email alerts
|

Effects of latitude and weather conditions on sugars, fruit acids and ascorbic acid in currant (Ribes sp.) cultivars

Abstract: BACKGROUND: Sugars, acids and vitamin C are essential components influencing the sensory and nutritional properties of currants (Ribes sp.). In this study the effects of growth latitude and weather conditions on these components in red, white and green currant cultivars were systematically investigated for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 49 publications
8
52
1
2
Order By: Relevance
“…The results regarding blackcurrant SS and sugar concentration revealed the significant effect of genotype, yet the cultivation method and yearly weather conditions played important roles in their accumulation, as indicated by other authors as well (Zheng et al, 2009a;Woznicki et al, 2015b). The highest average fruit SS and sugar concentrations were detected in the organically grown 'Karri', while the sugar concentration of the organic fruits of 'Mairi' remained on the same level with 'Karri' (Table 4).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The results regarding blackcurrant SS and sugar concentration revealed the significant effect of genotype, yet the cultivation method and yearly weather conditions played important roles in their accumulation, as indicated by other authors as well (Zheng et al, 2009a;Woznicki et al, 2015b). The highest average fruit SS and sugar concentrations were detected in the organically grown 'Karri', while the sugar concentration of the organic fruits of 'Mairi' remained on the same level with 'Karri' (Table 4).…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, in addition to taste-related compounds, the fruit weight is important, being a genotypedependent characteristic. Blackcurrant fruit quality and its nutritional value, including the concentration of AsA, sugars and organic acids depend on many factors such as genotype, latitude, cultivation conditions and agronomic practices (Anttonen and Karjalainen, 2006;Tabart et al, 2006;Pantelidis et al, 2007;Bordonaba and Terry, 2008;Brennan, 2008;Zheng et al, 2009a;2012;Walker et al, 2010;Krüger et al, 2011;Vagiri et al, 2014), but the effect of genotype on the berry quality and on the concentration of bioactive compounds has been considered as the most important (Krüger et al, 2011;Vagiri et al, 2013;Woznicki et al, 2015b), with different genotypes responding differently according to growth area and conditions (Zheng et al, 2009b). Diverse results have been described in different cultivation areas.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was found that betalains accumulation starts in the intermediate stage (half-done red violet), which resulted in losing lightness (L) and yellowness (b), but increased chroma was observed due to increase in redness (a) from green to red violet stages of B. rubra fruits. Decrease in lightness and increase in redness of fruits on maturation owing to accumulation of more pigments (Nergiz and Ergonul 2009) and wax (Zheng et al 2009) has been reported for various fruits, such as olive fruits and currant. Breakdown of chlorophyll and subsequent accumulation of pigments, such as carotenoids, anthocyanins and betalains have been associated with fruit colour change during ripening (Koning 1994;Khan and Giridhar 2014a).…”
Section: Pigment Characterizationmentioning
confidence: 95%
“…Вредност индекса сласти плодова, поред сортне предиспозиције зависи и од услова гајења (Zheng et al, 2009). * * * Многе студије су показале да се значајна антиоксидативна активност плодова рибизле и њихових прерађевина заснива на врло високим садржајима витамина С (Moyer et al, 2002).…”
Section: примарни метаболити плодова рибизлеunclassified
“…Вредност индекса сласти плодова, поред сортне предиспозиције, зависи и од услова гајења (Zheng et al, 2009). Од односа садржаја укупних шећера и киселина зависи укус плодова, који опет битно утиче на укупну органолептичку оцену.…”
Section: садржај шећера у плодовима сорти рибизлеunclassified